A scoping review of epidemiologic risk factors for pediatric obesity: Implications for future childhood obesity and dental caries prevention research. (10th June 2017) - Chi, Donald L.; Luu, Monique; Chu, Frances
Abstract: Research Questions: What are the non‐modifiable (socioeconomic, genetic) and modifiable factors (physical activity, dietary behaviors) related to childhood (under age 12) obesity? How can this knowledge be applied to oral health professionals' efforts to prevent or manage dental caries in children? Objectives: Studies have identified risk factors for childhood obesity. The purpose of this scoping review was to develop a conceptual model to identify non‐modifiable and modifiable risk factors for childhood obesity and to illustrate how these findings are relevant in developing interventions aimed at preventing obesity and dental caries in children. Methods: The authors searched PubMed and Embase and limited the study to English‐language publications. A total of 2, 572 studies were identified. After de‐duplication, 2, 479 studies remained and were downloaded into a citation‐management tool. Two authors screened the titles and abstracts for relevance. Two hundred and sixty studies remained and were retrieved for a full‐text review, and 80 studies were excluded, resulting in 180 studies included in the scoping review. An inductive content analytic methods was used to organize all statistically significant obesity risk factors into seven domains, which were classified as non‐modifiable or modifiable; then a conceptual model of common risk factors associated with childhood obesity and dental caries was developed. Results: Non‐modifiable obesity risk factors include biological and developmental (e.g., genes, developmental conditions, puberty), sociodemographic and household (e.g., race/ethnicity, socioeconomic status, parent education, unemployment), cultural (e.g., degree of acculturation), and community (e.g., neighborhood composition). Modifiable risk factors included behavioral (e.g., diet, physical activity, weight), psychosocial (e.g., maternal stress, family functioning, parenting practices, child temperament), and medical (e.g., parent smoking, maternal health, child health). Conclusions: Identifying common risk factors has important implications for future oral health research aimed at preventing childhood obesity and dental caries. Epidemiologic knowledge gleaned from the literature can be used to develop rigorous interventions and programs aimed at preventing these highly prevalent diseases and improving health outcomes for children.